The deeperning and its implication in Islamic religion learning (A study on" deeper learning: 7 powerful strategies for in depth and loger lasting learning" by Eric Jensen and leann nickelsen) - Fahmi Basa (Program Pasca Sarjana UIN Sunan Kalijaga, 2017)
yati 1/ws.c.1